Evaluasi Pemilihan Generator DC pada Sistem PLTA Portabel Skala Mikro untuk Suplai Energi Alat Berat di Daerah Terpencil: Studi Kasus Sungai Sumatera VIII - Muhammad Noviansyah Nugraha; Mutiara Putri (Department of Mechanical Engineering, Vocational College, Gadjah Mada University., 2025)
This study results in the performance of a DC generator in a portable hydroelectric power plant (PLTA) system designed using an Archimedes screw turbine. The main focus lies in the balance between the turbine's power capacity and the generator's ability to generate electrical energy efficiently. Based on the test results, there is a significant alignment between the theoretical power of the turbine (664.2 W) and the actual power produced by the generator (150 W). This evaluation aims to provide recommendations for selecting the right generator for a microhydro power plant system.